Roles of colloidal particles and soluble biopolymers in long-term performance and fouling behaviors of submerged anaerobic membrane bioreactor treating methanolic wastewater. (25th March 2021) - Lu, Xueqin; Zheng, Chaoting; Zhen, Guangyin; Tan, Yujie; Zhou, Yuhan; Zhang, Zhongyi; Niu, Chengxin; Li, Wanjiang; Kudisi, Dilibaierkezi; Wang, Yue; Li, Yu-You
Abstract: Anaerobic membrane bioreactor (AnMBR) has been applied as a promising technology for treating a variety of industrial wastewaters. Nevertheless, the potential of AnMBR for methanolic wastewater treatment is still not well recognized. In this study, a lab-scale AnMBR fed with low-strength methanolic wastewater was operated for 166 days with stepwise decreased HRT, and the roles of colloidal particles and soluble biopolymers in membrane fouling behaviors were elucidated comprehensively. The results showed that AnMBR showed the desirable performance and process stability with total chemical oxygen demand removal of 89.8 ± 1.1% and the highest methane production rate of 5.49 L/L-reactor/d at organic loading rate of 20.00 g-COD/L-reactor/d and hydraulic retention time of 18 h. The serious membrane fouling was observed after a period of operation at low HRT or high OLR due to the production of colloidal particles and the liberation of soluble biopolymers. Decreased particle size, and increased adhesion forces of gel-like flocs caused by the secretion of hydrophobic protein-bearing biopolymers accelerated the deposition of foulants and the formation of cake layer, inducing the easily mitigated membrane fouling. Further observations proved that the main bioconversion pathway of methanolic wastewater to biomethane was methylotrophic methanogenesis, followed by acetotrophic/hydrogenotrophic processes. Collectively, although the membrane fouling cannot be eliminated, this research confirmed the technical feasibility of AnMBR for methanolic wastewater treatment in real-world applications. Graphical abstract: Image 1 Highlights: Anaerobic membrane bioreactor was used for methanolic wastewater treatment. . The highest methane production of 5.49 L-CH4 /L/d was obtained at HRT 18 h. Colloidal organics blocked membrane pores, causing severe fouling. Methanomethylovorans was the main degrader of methanol.